TANTANGAN SUPRANASIONALITAS UNI EROPA: KOMPARASI INTEGRASI POLITIK PADA KRISIS EUROZONE 2008 DAN KRISIS PENGUNGSI 2015 - Demas Nauvarian (Indonesian Journal of International Relations, 2021)
The European Union is widely referred to as the international organization at the regional level with the highest integration phase. His journey is thought to have united the continent of Europe in a post-modern supranational political institution with a new post-Westphalia identity - European continental identity. This can be defined as a process of political integration. The process marked by the transfer of sovereignty, for example, can be seen in the European Union's ability to handle the Euro crisis in 2008. However, along the way, the political integration of the European Union is considered to be weakening. Post-Crisis 2008, the European Union experienced another challenge in the form of the 2014-2015 Refugee Crisis. This paper aims to answer questions related to why there is a weakening of the political integration of the European Union in these two challenges. By using the method of cross-longitudinal comparative studies on the responses of countries to the EU's decisions in the two challenges above, this paper argues that the increase in right-wing populism in various countries, particularly in Eastern and Central European countries, is a factor. the main part of the start to break up the political integration of the European Union. This paper concludes that the political values ​​of right-wing populism that focus on nation-state nationalism are contrary to the basic values ​​of the European Union which focus on liberal internationalism, and will become an obstacle to the future of EU political integration.